2016
DOI: 10.3389/fcell.2016.00040
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Signaling in Osteoblast Differentiation

Abstract: The skeleton is a highly dynamic tissue whose structure relies on the balance between bone deposition and resorption. This equilibrium, which depends on osteoblast and osteoclast functions, is controlled by multiple factors that can be modulated post-translationally. Some of the modulators are Mitogen-activated kinases (MAPKs), whose role has been studied in vivo and in vitro. p38-MAPK modifies the transactivation ability of some key transcription factors in chondrocytes, osteoblasts and osteoclasts, which aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
195
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(199 citation statements)
references
References 250 publications
(280 reference statements)
4
195
0
Order By: Relevance
“…The TGF-β/MAPK signaling pathway plays an important role in cell development, including differentiation, migration and proliferation [18]. ERK1/2 and ERK5, JNK1/2/3, and the p38 isoforms are members of the conventional MAPK family [19]. It was pointed out that ERK1/2 is activated by PI3K/Akt triggered by the binding of TGF-β with its receptors, indicating that TGF-β may induce MAPK proteins [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β/MAPK signaling pathway plays an important role in cell development, including differentiation, migration and proliferation [18]. ERK1/2 and ERK5, JNK1/2/3, and the p38 isoforms are members of the conventional MAPK family [19]. It was pointed out that ERK1/2 is activated by PI3K/Akt triggered by the binding of TGF-β with its receptors, indicating that TGF-β may induce MAPK proteins [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the p38/MAPK and MAPK/ERK signaling pathways are related to PDLSC self-renewal (Bernet et al, 2014;Sun et al, 2015;Rodríguez-Carballo et al, 2016). Therefore, western blotting was performed to detect related protein expression in PDLSCs after hypoxic culture for 48 h ( Figure 5).…”
Section: Hypoxia Activates P38/mapk and Mapk/erk Signaling Pathways Imentioning
confidence: 99%
“…We have previously demonstrated that TGF-β stimulates VEGF synthesis at least in part though the p38 MAP kinase activation in osteoblast-like MC3T3-E1 cells [28]. Nowadays, p38 MAP kinase is well recognized to be a crucial pathway in the TGF-β signaling in osteoblasts [29]. However, the exact mechanism behind TGF-β-induced VEGF synthesis in osteoblasts remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%